N-Heterocyclic carbene-catalyzed umpolung of imines for the enantioselective synthesis of dihydroquinoxalines - Das, Tamal Kanti; Ghosh, Avik; Balanna, Kuruva; Behera, Pradipta; Gonnade, Rajesh G.; Marelli, Udaya Kiran; Das, Abhijit Kumar; Biju, Akkattu T. (ACS Catalysis, 2019)
N-heterocyclic carbene (NHC) organocatalysis is widely employed for the umpolung of aldehydes and recently to the umpolung of Michael acceptors and aldimines. Described herein is the NHC-organocatalyzed umpolung of aldimines for the enantioselective synthesis of nitrogen heterocycles. The bisimines generated from the condensation of 1,2-phenylenediamines and salicylaldehydes undergo intramolecular cyclization in the presence of a chiral NHC catalyst, resulting in the formation of dihydroquinoxalines in moderate to good yields and er values. Detailed DFT studies shed light on the role of -OH groups in stabilizing the initially generated aza-Breslow intermediates via intramolecular hydrogen bonds. Preliminary photophysical studies on the synthesized dihydroquinoxalines revealed that these molecules can be used for the sensing of various acids and bases.
Keywords: dihydroquinoxalines; imines; N-heterocyclic carbenes; organocatalysis; umpolung

Dynamic kinetic resolution of gamma,gamma-disubstituted indole 2-carboxaldehydes via NHC-Lewis acid cooperative catalysis for the synthesis of tetracyclic epsilon-lactones - Balanna, Kuruva; Barik, Soumen; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (2022)
The ubiquity of epsilon-lactones in various biologically active compounds inspired the development of efficient and enantioselective routes to these target compounds. Described herein is the enantioselective synthesis of indole-fused epsilon-lactones by the N-heterocyclic carbene (NHC)-Lewis acid cooperative catalyzed dynamic kinetic resolution (DKR) of in situ generated gamma,gamma-disubstituted indole 2-carboxaldehydes. The Bi(OTf)(3)-catalyzed Friedel-Crafts reaction of indole-2-carboxaldehyde with 2-hydroxy phenyl p-quinone methides generates gamma,gamma-disubstituted indole 2-carboxaldehydes, which in the presence of NHC and Bi(OTf)(3) afforded the desired tetracyclic epsilon-lactones in up to 93% yield and >99 : 1 er. Moreover, preliminary studies on the mechanism of this formal [4 + 3] annulation are also provided.

N-heterocyclic carbene-catalyzed atroposelective synthesis of N-N axially chiral 3-amino quinazolinones - Balanna, Kuruva; Barik, Soumen; Barik, Shilpa; Shee, Sayan; Manoj, Niket; Gonnade, Rajesh G.; Biju, Akkattu T. (ACS Catalysis, 2023)
Although the atroposelective synthesisof biaryls and related compoundsbearing axially chiral C-C bonds is well-known, the synthesisof axially chiral C-N bond-containing compounds is relativelyless explored, and the construction of axially chiral N-N bondshas received only scant attention. Demonstrated herein is the N-heterocycliccarbene (NHC)-catalyzed selective amidation reaction, leading to theatroposelective synthesis of N-N axially chiral 3-amino quinazolinones.The NHC-catalyzed reaction of quinazolinones containing a free N-Hmoiety with & alpha;,& beta;-unsaturated aldehydes under oxidativeconditions furnished the atropisomeric quinazolinone derivatives undermild conditions and broad scope. Preliminary studies on experimentaland density functional theory-based N-N rotational barrierdetermination are also presented.
Keywords: amino quinazolinones; asymmetriccatalysis; axial chirality; N-heterocycliccarbenes; organocatalysis